Alocação ótima de equipamentos SVC e TCSC na rede de transmissão de energia elétrica - Sabillón Antúnez, Carlos Francisco [UNESP] (2014)
This research proposes a new approach for the problem of SVC and TCSC allocation in a trans- mission system. Since the rising of FACTS in the late 1970s, this type of devices had become a great tool in the search of solutions for the classic power transmission basic limitations. FACTS help to increase the controllability of flow over the lines and at the same time enhance the system stability. So, these devices can help in steady state augmenting the maximum power transfer among regions of the system and also, help in both the transient and dynamic stability of the system. Knowing the benefits that the FACTS provide to a transmission system, it is important to optimize this betterment. Several features must be taken into consideration to find an optimal location for FACTS in transmission systems such as device type, device size, total system power transfer and voltage and reactive power limit violations in the system. This work allocates two types of FACTS devices, the SVC (Static Variable Compensator) and TCSC (Thy- ristor Controlled Series Compensator). In the past, different approaches have been developed aiming to optimally allocate FACTS in a system. These approaches define their optimal loca- tion evaluating the benefits in steady state or the stability enhancement that the FACTS provide to the system. The objective and greatest contribution of this research is to find a solution for the problem of «optimal location of FACTS» that joins, evaluating in one objective function, both the steady state benefits and the dynamic benefits that the device provide to the system in a specific location. The objective function of the optimization model is calculated when a FACTS device is installed in a specific location. Its optimization criteria depend on the overall generation cost, total system losses, investment costs, maximum loading and system's transient stability. PSAT, a Matlab toolbox, is used to run the routines necessary to ...